Induction chemotherapy with cemiplimab in a patient with coexistent vulvar cancer and autoimmune disease: A case report - Elizabeth G. Thayer; M. Larissa Weirich; Zoe A. Roecker; Sara E. Brenner; Jill S. Remick; Ashish B. Patel; Kristen D. Starbuck (Elsevier, 2024)
There is limited data regarding the use of immunotherapy for patients with vulvar squamous cell carcinoma and coexisting autoimmune disease. Cemiplimab is a PD-1 inhibitor approved for use in patients with locally advanced and metastatic cutaneous squamous cell carcinoma. However, little is known about its efficacy in the setting of vulvar cancer. We present a case of advanced vulvar squamous cell carcinoma treated with induction chemotherapy and immunotherapy with cemiplimab followed by definitive chemoradiation in the setting of multiple autoimmune diseases. She achieved a complete clinical response and experienced no worsening of her autoimmune conditions despite cessation of her immunosuppressants and initiating an immune checkpoint inhibitor. We review existing data on neoadjuvant treatment of vulvar cancer and the use of cemiplimab in genital and inguinal squamous cell carcinomas. Ongoing exploration of cemiplimab's efficacy in vulvar cancer and safety in immunosuppressed patients is critical.